The Unstable Elbow : An Evidence-Based Approach to Evaluation and Management - Tashjian, Robert Z. (Springer International Publishing : Imprint: Springer, 2017)
Providing a detailed review of one of the most common clinical problems, elbow instability, this comprehensive text organizes the most up-to-date, evidence-based information on the rapidly advancing field of elbow surgery. Initial chapters focus on anatomy, biomechanics and the most currently utilized surgical approaches for the treatment of the unstable elbow. Subsequent chapters focus on the evaluation and surgical treatments of acute instabilities, such as simple dislocations and fracture-dislocations, as well as chronic instabilities, including chapters focusing on the non-operative and operative management of the throwing athlete. The final chapters describe additional treatment strategies for complex instabilities, focusing on external fixation, total elbow arthroplasty and elbow fusion. Each chapter includes background information, an evaluation section, a treatment algorithm, non-operative treatment strategies, surgical management, published outcomes and preferred methods of treatment from each author. A supplemental video section is also included, depicting frequently performed procedures. Written by experts in the field, The Unstable Elbow consolidates all of the current knowledge of elbow instability into a valuable resource for orthopedic surgeons and residents worldwide.
Keywords: Medicine.; Rheumatology.; Orthopedics.; Sports medicine.; elektronické knihy; electronic books